2020
DOI: 10.3892/ijmm.2020.4771
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic landscaping of core genes and pathways of mild and severe psoriasis vulgaris

Abstract: Psoriasis is a common chronic inflammatory skin disease affecting >125 million individuals worldwide. The therapeutic course for the disease is generally designed upon the severity of the disease. In the present study, the gene expression profile GSE78097, was retrieved from the National Centre of Biotechnology (NCBI)-Gene Expression Omnibus (GEO) database to explore the differentially expressed genes (DEGs) in mild and severe psoriasis using the Affy package in R software. The Kyoto Encyclopaedia of Genes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…13,32 Indeed, Choudhary et al even demonstrated that CCNB1 is one of the central targets of severe psoriasis. 14 However, to date, the potential pathological mechanisms of CCNB1 and CCNB2 in psoriasis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,32 Indeed, Choudhary et al even demonstrated that CCNB1 is one of the central targets of severe psoriasis. 14 However, to date, the potential pathological mechanisms of CCNB1 and CCNB2 in psoriasis remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Bioinformatics analyses by Choudhary and Melero showed that CCNB1 is a core target in the onset mechanism of psoriasis and may contribute to the transformation of mild to severe psoriasis. 14,15 Furthermore, Li et al. showed that CCNB2 expression ameliorates the symptoms of psoriasis patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that Ps deregulated genes were found. These genes are involving cytokine-cytokine receptor interaction, cell cycle and cell adhesion molecules and these candidate genes regulating important immune pathways can be new therapeutic targets in Ps [96]. There are more than 50 genetic susceptible biomarkers associated with the risk of Ps.…”
Section: Immune Molecules As Biomarkers In Psoriasismentioning
confidence: 99%
“…In recent years, new insights into the molecular mechanisms and therapeutic targets of psoriasis have been provided by bioinformatics analysis ( 10 ). A pooled analysis of DEGs in psoriasis will remind us of the etiology of the disease, as these DEGs may reflect the common skin reactions that occur in many skin diseases in the absence of common causal mechanisms, and prognostic analyses have no evidence of significant differences between patients treated with guselkumab ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%